Photo-physical characterization of high triplet yield brominated fluoresceins by transient state (TRAST) spectroscopy - Demirbay Baris; Baryshnikov Glib; Haraldsson Martin; Ågren Hans; Piguet Joachim; Widengren Jerker (Royal Institute of Technology, 2023)
This folder contains all raw data underlying the results presented in a manuscript, submitted for publication to Methods and Applications in Fluorescence, and entitled:

Photo-physical characterization of high triplet yield brominated fluoresceins by transient state (TRAST) spectroscopy

Authored by:

Baris Demirbaya, Glib Baryshnikovb, Martin Haraldssonc, Joachim Pigueta, Hans Ågrend, Jerker Widengrena,*

aRoyal Institute of Technology (KTH), Experimental Biomolecular Physics, Department of Applied Physics, Albanova University Center, SE-106 91, Stockholm, Sweden

bLaboratory of Organic Electronics, Department of Science and Technology, Linköping University, SE-60174, Norrköping, Sweden

cChemical Biology Consortium Sweden, Science for Life Laboratory, Department of Medical Biochemistry and Biophysics, Karolinska Institute, SE-171 77 Stockholm, Sweden

dDepartment of Physics and Astronomy, Uppsala University, SE-751 20 Uppsala, Sweden

*Corresponding Author:

Email:  jwideng@kth.se, Phone: +46-8-7907813

The data files are grouped into the different techniques used to generate them, and refer to the figures/tables in the manuscript where the extracted results are presented.

ABSTRACT

Photo-induced dark transient states of fluorophores can pose a problem in fluorescence spectroscopy, but their typically long lifetimes can also make them highly environment sensitive. This opens for exploiting these states as microenvironmental read-out parameters in bio-molecular spectroscopy and imaging, and to explore fluorophores with prominent dark-state formation yields to be used in such studies. In this work, we analyzed the singlet-triplet transitions of fluorescein by transient state (TRAST) spectroscopy and compared them with those of three synthesized carboxy-fluorescein derivatives, with one, two or four bromines linked to the anthracence backbone. By this bromination, a prominent internal heavy atom (IHA) enhancement of the intersystem crossing (ISC) rates was found, and a corresponding external heavy atom (EHA) enhancement upon adding potassium iodide (KI) into the fluorophore solutions. Notably, increased KI concentrations still resulted in lowered triplet state buildup in the brominated fluorophores, due to the relatively lower increase induced in the ISC, than in the triplet decay. Moreover, KI had an antioxidative effect on the fluorophores, resulting in an overall fluorescence enhancement of the brominated fluorophores. The mechanisms behind the prominent IHA effect were further investigated by density functional theory calculations, which suggest that the ISC likely takes place to a higher triplet state, followed by relaxation to the lowest triplet state.

By TRAST measurements, performed under biologically relevant conditions and analyzing how the average fluorescence intensity of fluorescent molecules varies with a systematically varied excitation modulation, dark state transitions within very high triplet yield (>90%) fluorophores can be directly analyzed, as well as IHA and EHA effects. These measurements, not possible by other techniques such as fluorescence correlation spectroscopy, opens for bio-sensing applications based on high triplet yield fluorophores, and for characterization of high triplet yield photodynamic therapy agents, and how they are influenced by IHA and EHA effects.
Keywords: Fluorescence, fluorescein, bromination, triplet state, heavy atom effect, intersystem crossing; Physical Sciences; Fysik